Does internal branding boost brand endorsement and brand-supporting behavior? The role of brand knowledge - Suryana Hendrawan; Christina Whidya Utami; Budi Barata Kusuma Utami; Rikha Muftia Khoirunnisa; Wei Zhao (Universitas Ahmad Dahlan, 2026)
Purpose-This study aims to examine how internal branding influences brand endorsement and brand-supporting behavior, with brand knowledge serving as a mediating variable. This study is motivated by the need to understand the extent to which internal brand management can transform employees into brand advocates and endorsers on the front lines of service, while addressing the limitations of previous research, which generally examined internal branding, brand knowledge, and brand-supporting behavior separately. Methodology-A quantitative study with 107 employees from 3–5-star hotels who interact directly with guests, selected through purposive sampling. Data were analyzed using partial least squares structural equation modeling to test the relationships among internal branding, brand knowledge, brand endorsement, and brand-supporting behavior. Findings-Internal branding has a positive effect on brand endorsement, brand knowledge, and brand-supporting behavior. Brand knowledge has a significant effect on brand endorsement and brand-supporting behavior, but with a negative coefficient that deviates from the direction of the relationship typically predicted by theory, while simultaneously forming a significant mediating path between internal branding and both behaviors. Research Limitations-The study was conducted only at star-rated hotels in Yogyakarta, Indonesia, using a cross-sectional design and self-report instruments; therefore, the results may not represent the entire hospitality industry or other regions and remain susceptible to respondent perception bias. Novelty-This study contributes by simultaneously testing internal branding, brand knowledge, brand endorsement, and brand-supporting behavior within a single model in the context of hotels in Indonesia. This area has not been extensively studied. The results open opportunities for further research to test this model in other types of hospitality businesses, to add new mediator or moderator variables, and to highlight the dynamics in which increased brand knowledge may be negatively associated with brand-supporting behavior—a relationship relatively rarely explored in previous literature.